2016
DOI: 10.1128/aac.02639-15
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Activity of Combined NS5A Inhibitors

Abstract: ). To extend the characterization of NS5 A synergists, we tested new combinations of DCV and NS5A synergists against genotype (gt) 1 to 6 replicons and gt 1a, 2a, and 3a viruses. The kinetics of inhibition in HCV-infected cells treated with DCV, an NS5A synergist (NS5A-Syn), or a combination of DCV and NS5A-Syn were distinctive. Similar to activity observed clinically, DCV caused a multilog drop in HCV, followed by rebound due to the emergence of resistance. DCV-NS5A-Syn combinations were highly efficient at c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…This is supported by a previous manuscript that shows the synergistic effect between the NS5A inhibitor daclatasvir and other NS5A inhibitors [ 25 ].…”
Section: Resultssupporting
confidence: 83%
“…This is supported by a previous manuscript that shows the synergistic effect between the NS5A inhibitor daclatasvir and other NS5A inhibitors [ 25 ].…”
Section: Resultssupporting
confidence: 83%
“…This result represented a 2,600-fold increase in the sensitivity of the Tyr93Asn replicon to 1 in the presence of 52. The synergistic relationship between 1 and 52 was confirmed in a reciprocal experiment where 52 was titrated in the presence of suboptimal amount of 1 affording a similar outcome [60,61].…”
Section: Mode Of Action Studies With Daclatasvirmentioning
confidence: 77%
“…These studies have suggested that the binding of inhibitors to NS5A interferes with the association of viral RNA with the protein, with the binding of compounds competed out by other NS5A inhibitors and demonstrating diminished affinity for the Tyr93His mutant protein [58,59]. However, profiling of inhibitors in cell-based assays has indicated that disruption of RNA binding to NS5A does not appear to occur and that the introduction of key resistant mutations leads to only a modest reduction in the binding of inhibitors [60,61]. Studies with 50 in resistant GT-1b replicons indicated that while the Tyr93His-resistant mutation reduced inhibitory potency by 220-fold, an estimate of the amount of NS5A protein pulled down by the chemical probe, as determined by an analysis of Western blots, suggested similar levels of protein-drug association for the resistant and wild-type strains [60,61].…”
Section: Mode Of Action Studies With Daclatasvirmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, emergence of DAA RAVs is yet a major drawback of DAAs. To overcome this, combination therapies using DAAs become now representative approaches for HCV treatment 10 15 . Nevertheless, new combination therapies still need to be developed for patients with RAVs who do not respond to current DAAs and for those with difficult-to-treat HCV genotypes such that alternative or advanced treatment options can be provided for better management of HCV infection 4 .…”
Section: Introductionmentioning
confidence: 99%